A CARD9 Founder Mutation Disrupts NF-κB Signaling by Inhibiting BCL10 and MALT1 Recruitment and Signalosome Formation - De Bruyne, Marieke; Hoste, Levi; Bogaert, Delfien J.; Van den Bossche, Lien; Tavernier, Simon J.; Parthoens, Eef; Migaud, Mélanie; Konopnicki, Deborah; Yombi, Jean Cyr; Lambrecht, Bart N.; van Daele, Sabine; Alves de Medeiros, Ana Karina; et al. (Frontiers in Immunology, 2018)
Background: Inherited CARD9 deficiency constitutes a primary immunodeficiency predisposing uniquely to chronic and invasive fungal infections. Certain mutations are shown to negatively impact CARD9 protein expression and/or NF-κB activation, but the underlying biochemical mechanism remains to be fully understood. Objectives: To investigate a possible founder origin of a known CARD9 R70W mutation in five families of Turkish origin. To explore the biochemical mechanism of immunodeficiency by R70W CARD9. Methods: We performed haplotype analysis using microsatellite markers and SNPs. We designed a model system exploiting a gain-of-function (GOF) CARD9 L213LI mutant that triggers constitutive NF-κB activation, analogous to an oncogenic CARD11 mutant, to study NF-κB signaling and signalosome formation. We performed reporter assays, immunoprecipitation and confocal imaging on HEK cells overexpressing different CARD9 variants. Results: We identified a common haplotype, thus providing evidence for a common Turkish founder. CARD9 R70W failed to activate NF-κB and abrogated NF-κB activation by WT CARD9 and by GOF CARD9. Notably, R70W CARD9 also exerted negative effects on NF-κB activation by CARD10, CARD11 and CARD14. Consistent with the NF-κB results, the R70W mutation prevented GOF CARD9 to pull down the signalosome partner proteins BCL10 and MALT1. This reflected into drastic reduction of BCL10 filamentous assemblies in a cellular context. Indeed, structural analysis revealed that position R70 in CARD9 maps at the putative interface between successive CARD domains in CARD9 filaments. Conclusion: The R70W mutation in CARD9 prevents NF-κB activation by inhibiting productive interactions with downstream BCL10 and MALT1, necessary for assembly of the filamentous CARD9-BCL10-MALT1 signalosome.